The Impact of Brand Hate and Negative E-WOM on Non Purchase Intention (Case Study on American Food) - Slamet, Frima Agustian; Yuliana, Lingga (Pusat P2M Politeknik Negeri Batam, 2024)
The purpose of this study is to examine how brand hate and negative electronic word-of-mouth affect consumers' intentions not to buy. This study focuses on a particular category of food product from the American brand McDonald's (McD). In this study, which included 123 respondents from Jabodetabek, the methodology was quantitative. Responses have to be both male and female, between the ages of 17 and 55, and have to be up to date on the terms of Israel's and Palestine's conflict. By using Google Form as a intermediate platform to distribute questionnaires, the data source uses primary data. Leveraging the SmartPLS version 4.1.0.0 tool, the partial least squares data analysis technique is used. The first finding of the study is that brand hate significantly and favorably affects consumers' intentions not to buy. Second, non-purchase intention is positively and significantly impacted by negative electronic word-of-mouth.